Particularities of structure formation of aluminum-copper composite materials manufactured by casting technology - V. A. Kalinichenko; A. S. Kalinichenko; S. V. Grigoriev (Литьë и металлургия)
To create friction pairs operating in severe working conditions, composite materials are now increasingly used. Composite materials obtained with the use of casting technologies are of interest due to the possibility to manufacture wide range of compositions at low price compared to powder metallurgy. Despite the fact that many composite materials have been sufficiently studied, it is of interest to develop new areas of application and give them the properties required by the consumer. In the present work the composite materials on the basis of silumin reinforced with copper granules were considered. Attention was paid to the interaction between the matrix alloy and the reinforcing phase material as determining the properties of the composite material. The analysis of distribution of the basic alloying elements in volume of composite material and also in zones of the interphases interaction is carried out. The analysis of the possibility of obtaining a strong interphase zone of contact between the reinforcing component and the matrix material without significant dissolution of the reinforcing material is carried out.